Development and validation of a novel necroptosis-related score to improve the outcomes of clear cell renal cell carcinoma - Chen, Ji; Tao, Qiqi; Lang, Zhichao; Jin, Yan; Chen, Guanqi; Li, Xinling; Yu, Zhixian; Li, Yeping (Frontiers in Genetics, 2022)
Necroptosis has been indicated as a key regulator of tumor progression. However, the prognostic regulatory role of necroptosis in clear cell renal cell carcinoma (ccRCC) needs to be further investigated. In this study, necroptosis-related subtypes were identified by mining the public cohort (n = 530) obtained from The Cancer Genome Atlas. By applying Principal Component Analysis (PCA), the necroptosis-related scores (N-Score) were developed to assess the prognosis procession of ccRCC. The results were further validated through the external clinical cohort (n = 116) obtained from the First Affiliated Hospital of Wenzhou Medical University. It has been found that N-Score could precisely distinguished the prognostic of patients as an independent risk factor (Hazard ratio=4.990, 95% CI=2.007-12.403, p<0.001). In addition, changes in N-Score corresponded with differences in tumor mutational burden as well as immune infiltration characterization. Moreover, higher N-Scores also predicted significantly molecular drug sensitivity and stronger immune checkpoint activity. Notably, the prognosis of ccRCC can be effectively guided by combining the N-Scores and external clinical indicators. In conclusion, N-Scores could be served as a robust and effective biomarker to improve the prognosis outcomes and targeted therapy of ccRCC.